Skeletal characteristics differ between Division I male basketball and cross-country athletes - Wunderlich, L.; Goulart, J.; Mroz, K.; Sekel, N.; Sterczala, A.; Feigel, E.; Cauley, J.; Fazeli, P.; O'Leary, T.; Greeves, J.; Koltun, K.; Nindl, B. (International Journal of Exercise Science Conference Proceedings, 2025)
Bone is a mechanosensitive tissue that will adapt based on the specific loading demands of a given sport. PURPOSE To compare skeletal characteristics between high-level male athletes participating in high-impact vs. repetitive low impact sports. METHODS High-resolution peripheral quantitative computed tomography (HR-pQCT) assessed volumetric bone mineral density (vBMD) and microarchitecture at the distal tibial metaphysis (4%) and diaphysis (30%) in NCAA Division I men`s basketball (BB; n=15, 20.7±1.8 yrs, 24.5±3.6 kg/m2 ) and cross-country athletes (XC; n = 14, 19.3±1.6 yrs, 21.1±1.6 kg/m2 ). Finite element analysis quantified whole bone stiffness and estimated strength. Dual energy X-ray absorptiometry (DXA) measured areal BMD (aBMD) of the total body, hip, and lumbar spine. HR-pQCT variables were compared via ANCOVAs, with tibia length as a covariate. Independent samples t-tests or Mann-Whitney U tests compared aBMD and demographic variables; a=0.05. RESULTS BB athletes were older (mean difference (MD)=1.4 yrs, p=0.032), taller (MD=6.3 in, p<0.001), and heavier (MD= 56.4 lbs, p<0.001) than XC. After adjusting for tibia length (MD=64.8 mm, p<0.001), BB athletes exhibited greater total vBMD (BB=328.9±32.4 mg/cm3 , XC=273.3±28.3 mg/cm3, p=0.003) trabecular (Tb) vBMD (BB= 270.2±24.5 mg/cm3, XC=236.9±23.2 mg/cm3, p=0.005), Tb bone volume fraction (BB=0.40±0.04, XC=0.35±0.04, p=0.006), Tb number (BB=2.2±0.2 1/mm, XC=1.9±0.18 1/mm, p=0.014), stiffness (BB=4.3x105±9.1x104 N/mm, XC=2.8x105±4.9x104 N/mm, p=0.007), and failure load (BB=-2.3x104±4.7x103 N, XC=-1.5x104±2.5x103 N, p=0.007) at the tibial metaphysis; XC had greater Tb separation (XC=0.47±0.052 mm, BB=0.41±0.042 mm, p=0.021). At the diaphyseal tibia, BB had greater cortical (Ct) area (BB=398.3±40.6mm2, XC=319.6±35.3 mm2, p=0.041), Ct vBMD (BB=1009.3 ±18.3 mg/cm3 , XC=981.6±14.2 mg/cm3 p=0.002), stiffness (BB=4.3x105±4.5x104 N/mm, XC=3.4x105±3.9x104 N/mm, p=0.046), and failure load (BB=-2.4x104±2.6x103 N, XC=1.9x104±2.2x103 N, p=0.049). aBMD of the total body (MD=0.2 g/cm2, p<0.001), total hip (MD=0.3 g/cm2 , p<0.001), femoral neck (MD=0.4, p<0.001), and lumbar spine (MD=0.3 g/cm2, p<0.001) were greater in BB athletes. CONCLUSION BB athletes, who participate in high impact loading as part of sporting activity, demonstrate greater two- and three-dimensional BMD, as well as more favorable bone microarchitecture and strength of the lower leg compared to athletes participating in lowimpact sports (i.e., XC). SIGNIFICANCE/NOVELTY Given the more favorable bone parameters observed in basketball athletes compared to cross-country athletes, participation in sports that require intermittent multidirectional loading can foster the development of a stronger more resilient skeleton.